Pendampingan Kegiatan Tajribah Mahasiswa UNU Sunan Giri Bojonegoro di Kecamatan Kopohbaru Bojonegoro - Zaini Miftah (TAAWUN, 2021)
The term Tajribah is experience, which actually means experiment and experience which in this case is carried out by lecturers and students who collaborate with Islamic boarding schools to carry out various activities. This activity is carried out to find out and at the same time preach in the midst of community needs related to educational and social problems. Starting from the transect that was carried out to the mapping of activities to the evaluation carried out, it showed that the community really needed assistance for the problems found. In the implementation of this activity using the ABCD (Asset Based Community Development) method. The ABCD approach is an approach and paradigm in community service programs that have an approach principle that all leads to the context of understanding and internalizing assets, potentials, strengths, and utilizing them independently and maximally. And from the results of this activity, it can be seen that the enthusiasm of the community is very high with the support from various parties.This result is evidenced by statistical data using a Likert scale with a total of 100 respondents. From the results of the calculations used indicate that this activity is very useful with the results of 88.75% which means the results are "Very Good"